Gestión de planillas electrónicas y el cumplimiento de las obligaciones tributarias laborales en la unidad de gestión educativa local Contamana, 2023 - Vela Rengifo, Terry Gerson (2023)
The objective of this thesis report was to determine the relationship between electronic payroll management and compliance with labor tax obligations in the Contamana Local Educational Management unit, 2023, where an applied study was used, descriptive-correlational and design level. non-experimental, taking as a population 65 public servants to whom a questionnaire was applied. After analyzing the results, it was determined that the management of electronic payrolls is regular, this is because there is a reliable record of workers that serves as a labor inspection mechanism; Additionally, statutory discounts tend to be processed in a timely manner. Regarding compliance with labor tax obligations, it is rated as average, since payments of basic remuneration and unpaid vacations are made intermittently. Determining that there is a significant relationship between the variables, demonstrated by a considerable coefficient of 0.809 and a significance of 0.000.